KONSEP PENDIDIK DAN METODE PEMBELAJARAN YANG HUMANIS MENURUT IBNU KHALDUN - Kiki Sumber Rejeki (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2020)
This study aims to find out and analyze the concept of educators and humanist learning methods according to Ibn Khaldun in his book entitled